1993
DOI: 10.1902/jop.1993.64.10.980
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Interleukin‐6 in Gingival Crevicular Fluid From Adults With Destructive Periodontal Disease

Abstract: This paper describes a study of whether or not the amounts of interleukin‐6 (IL‐6) in gingival crevicular fluid (GCF) are correlated with periodontal clinical measures. A sensitive ELISA was developed to measure IL‐6 in GCF. Two male and 3 female adult subjects with periodontal disease were examined at their first appointments, after 3 months, and after 6 months. Data were obtained on plaque index (PI), bleeding index (BI), probing depth (PD), and on the IL‐6 content of GCF samples from 16 sites per subject fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
123
3
8

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(147 citation statements)
references
References 12 publications
9
123
3
8
Order By: Relevance
“…Reduction of SOCS levels also increased the activation status of Stat3, a transcription factor that binds to IL-6-responsive promoter elements (27). P. gingivalis can stimulate the production of IL-6 from gingival epithelial cells (47), and IL-6 levels are elevated in gingival crevicular fluid in periodontal disease (14,26). Hence, induction of miR-203 by P. gingivalis has the potential to contribute to the inflammation associated with periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of SOCS levels also increased the activation status of Stat3, a transcription factor that binds to IL-6-responsive promoter elements (27). P. gingivalis can stimulate the production of IL-6 from gingival epithelial cells (47), and IL-6 levels are elevated in gingival crevicular fluid in periodontal disease (14,26). Hence, induction of miR-203 by P. gingivalis has the potential to contribute to the inflammation associated with periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to normal tissue, IL-6 expression appears to be elevated in inflamed tissue from periodontitis sites and is highest in gingivitis sites (33,59). Studies have indicated that IL-6 levels are higher in GCF from refractory periodontitis patients and may also correlate with progression of disease in these patients (13,29,45). IL-6 stimulates plasma cell proliferation and therefore may promote the presence of plasma cells that are readily found in periodontitis lesions (47).…”
Section: Discussionmentioning
confidence: 99%
“…High amounts of IL-6 were detected in patients with periodontitis (21,22), in active sites of refractory periodontitis (23), as well as in sites undergoing orthodontic movement, emphasizing the important role of IL-6 in the bone remodeling process (24). IL-6 was observed to correlate with the severity of periodontal disease (25), which may indicate that IL-6 could be a diagnostic marker for sites of active periodontal disease (26).…”
Section: Discussionmentioning
confidence: 95%